ANALISIS SISTEM DINAMIK NERACA AIR DI PULAU TIDORE - Malaka, Halima; Yanuar, M.; Purwanto, J.; Zein, Alinda (Jurnal Air Indonesia, 2015)
This research was conducted at Tidore Island, –Tidore City, North Maluku Archipelago Province. Objective of this study were 1) build a water balance model Tidore Island. This Method used in this research is method of survey with water balance analysis. Analysis of the data used is the analysis of dynamic system to determine the balance of the year 2009 - 2032 with software stella version 9.0.2. The result of analysis showed that in 2009 there were water balance 21,189,941.20 m3 / year and in 2032 there was a deficit of 427,678.61 m3 / year. Water availability index (IKA) in 2009 amounted to 1416.10 and in the year 2032 amounted to 82.54 IKA the value, it indicates that in 2032 the availability of groundwater only able to serve 82.54% the water demand. To improve the balance of water needed for water saving and conservation policies at each land use.Saving measures water use and conservation of groundwater done using three policy scenarios, the model simulation results indicate that both scenarios can increase the efficiency of water use and water balance in 2009 to 21,270,444.14 m3 / year with a value of 1490.63 and value IKA in 2032 can be water deficit of 31128.46 m3 / year. While the results of the simulation scenario 3 scenario between saving integrated water use and conservation can improve the water balance in 2009 amounted to 21,350,947.08 m3 / year and the value IKA 1573.44, and in 2032 the value decreased to 117.92 IKA shows the availability of ground water able to serve 117.92% of water demand people. Keywords: water balance,system dynamic, water demand, ground water availability